2008
DOI: 10.12973/ejmste/75302
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Elementary School Teachers’ Learning Styles and Attitudes towards Mathematics

Abstract: The purpose of this study was to investigate the differences of pre-service elementary school teachers' attitudes towards mathematics according to their learning styles. Two hundreds eighty one pre-service elementary school teachers were involved in this study. The researchers employed two types of instruments, Learning Style Inventory and Scale of Mathematics Attitude Questionnaire, to collect the data. The learning style inventory was designed to detect the participants' learning styles, Divergent, Assimilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 7 publications
1
22
0
10
Order By: Relevance
“…As pre-service teachers' mathematics teaching anxiety levels decrease, the differences among preservice teachers according to different variables may disappear, because the main purpose is to make sure that every pre-service teacher learns at an optimum and equal level together with others. Like many other researchers (Morris & McCarthy, 1990;Harb, Durrant, & Terry, 1993;Knisley, 2002;Peker & Mirasyedioğlu, 2008) I hope that the learning cycle (or 4 MAT system) constructed according to different learning styles will improve mathematics achievement and attitudes towards mathematics teaching among pre-service teachers. Pre-service teachers can find that all the features of the four learner types, and the difference between their mathematics teaching anxieties depending on learning styles, can be eliminated by applying the 4 MAT system.…”
Section: Recommendations and Future Researchmentioning
confidence: 80%
See 2 more Smart Citations
“…As pre-service teachers' mathematics teaching anxiety levels decrease, the differences among preservice teachers according to different variables may disappear, because the main purpose is to make sure that every pre-service teacher learns at an optimum and equal level together with others. Like many other researchers (Morris & McCarthy, 1990;Harb, Durrant, & Terry, 1993;Knisley, 2002;Peker & Mirasyedioğlu, 2008) I hope that the learning cycle (or 4 MAT system) constructed according to different learning styles will improve mathematics achievement and attitudes towards mathematics teaching among pre-service teachers. Pre-service teachers can find that all the features of the four learner types, and the difference between their mathematics teaching anxieties depending on learning styles, can be eliminated by applying the 4 MAT system.…”
Section: Recommendations and Future Researchmentioning
confidence: 80%
“…For example, Peker (2005) found that learning style was a good predictor of mathematics achievement for pre-service teachers. Peker and Mirasyedioğlu (2008) found significant differences in attitudes towards mathematics among pre-service elementary school teachers with different learning styles. Besides, Hadfield and Maddux (1988), Hadfield, Martin, and Wooden (1992), and Sloan, Daane, and Giesen (2002) claimed that learning styles were related to mathematics anxiety.…”
Section: Learning Stylesmentioning
confidence: 85%
See 1 more Smart Citation
“…A lot of research supports the positive role that students' attitudes toward mathematics plays in their academic achievement and careers in the mathematical sciences [3] [6] [13]. Buckley argued that if a student enjoys in class they will be motivated to invest more effort in that class and perhaps future classes and they will learn more effectively [1].…”
Section: Student Attitudes Toward Mathematicsmentioning
confidence: 99%
“…Teachers' attitudes toward mathematics also affect their teaching of mathematics (Ma, 1997;Gellert, 1999;Lee, 2005;Brown, 2005;Brown et al, 2008;Sweeting, 2011). Moreover, it is thought that teachers' negative attitudes towards mathematics affects children's attitudes towards mathematics (Bush, 1989;Bursal & Paznokas, 2006;Malinsky, Ross, Pannells, & McJunkin, 2006;Peker & Mirasyedioğlu, 2008;Gresham, 2008;Peker, 2009). There is research that suggests a relationship between the qualifications of teachers and their children's academic achievements (Roberts et al, 1998;Brown et al, 2008;Thornton, 2009).…”
Section: Introductionmentioning
confidence: 99%